Cypermethrin resistance in Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) from three locations in Thailand and detoxification enzyme activities - Ruttanaphan, Torranis; Pluempanupat, Wanchai; Bullangpoti, Vasakorn (Agriculture and Natural Resources, 2018)
The tobacco cutworm Spodoptera litura is one of the key insect pests of vegetables in Thailand. This study evaluated cypermethrin resistance in populations of S. litura collected from vegetable crops in Bang Len and Kamphaeng Saen district, Nakhon Pathom province and from Wang Nam Khiao district, Nakhon Ratchasima province, Thailand. Resistance of S. litura was determined using the topical application method and biochemical assays, and all three field populations exhibited a trend of increasing resistance to cypermethrin compared to the susceptible laboratory population, with median lethal dose (LD50) values varying from 10.98 parts per million (ppm) to 15.74 ppm. The activities of cytochrome P450 monooxygenase and carboxylesterase in field populations of S. litura were significantly increased compared to those in susceptible insects, but glutathione S-transferase activity was significantly increased only in the Kamphaeng Saen population. These results indicated that the three field populations of S. litura had developed resistance to cypermethrin and it is suggested that continuous application of cypermethrin to control tobacco cutworm should be avoided to prevent the development of high cypermethrin resistance in this pest.